2014
DOI: 10.5935/1678-9741.20140050
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gender on the early results of coronary artery bypass surgery in younger patient group

Abstract: IntroductionIn this retrospective study, we aimed to determine the risk factors for coronary artery bypass surgery in patients under 45 years of age, and evaluate the early postoperative results and the effect of gender.MethodsA total of 324 patients under 45 years of age who undergone on-pump coronary artery bypass surgery between April 12, 2004 and January 10, 2012 were included to the study. Patients divided into groups as follows: Group 1 consisted of 269 males (mean age 41.3), Group 2 consisted of 55 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…There is also inconsistency between gender difference and postoperative outcomes following CABG in the previous studies when examined and compared with each other. In many studies female gender was found associated with worse postoperative outcomes after CABG surgery [ 8 - 11 ] , while in some other studies which especially had the propensity-matching for the adjustment of risk factors, demonstrated that the outcomes in females were similar to their matched male counterpart following CABG [ 12 - 15 ] . Thus, the impact of gender difference on postoperative outcomes after CABG is a debated topic of ongoing relevance.…”
Section: Introductionmentioning
confidence: 99%
“…There is also inconsistency between gender difference and postoperative outcomes following CABG in the previous studies when examined and compared with each other. In many studies female gender was found associated with worse postoperative outcomes after CABG surgery [ 8 - 11 ] , while in some other studies which especially had the propensity-matching for the adjustment of risk factors, demonstrated that the outcomes in females were similar to their matched male counterpart following CABG [ 12 - 15 ] . Thus, the impact of gender difference on postoperative outcomes after CABG is a debated topic of ongoing relevance.…”
Section: Introductionmentioning
confidence: 99%
“…Летальность у женщин была выше -4,60% vs 2,53% (р<0,0001), что связано с более старшим возрастом, наличием сахарного диабета, хронической болезни почек 3-5 стадии и ХОБЛ [16]. В то же время в исследовании [17] не выявлено гендерных различий послеоперационной летальности при АКШ в возрастной группе <45 лет [17]. При этом по данным [6] о валидности ES при наблюдении 46516 пациентов после кардиохирургических вмешательств в Швеции в период 2001-2007гг, риск 30-суточной летальности составил 3,2% [6].…”
Section: результаты и обсуждениеunclassified
“…[28] found a much higher percentage of smokers among patients undergoing coronary artery bypass graft surgery: male (59.9%) and females (40%). However, the study recruited a young cohort of below 40 years of age, which could explain the higher percentages of smokers.…”
Section: Relationship Between Infected and Non-infected Casesmentioning
confidence: 99%
“…However, study in New Zealand found more women (20.2%) smokers among patients undergoing coronary artery bypass graft surgery compared to male patients (13.1%) [29]. Smoking is a significant risk factor leading to the advancing of surgical site infection and other risk factors such as myocardial infarction, reoperation, and angina pectoris [28].…”
Section: Relationship Between Infected and Non-infected Casesmentioning
confidence: 99%